Fracture toughness enhancement of silicon carbide composites with hydrophilic-modified Tyranno® Si–Al–C fibre addition - Moriyasu, H.; Davies, Ian; Itatani, K. (Maney Publishing, 2017)
© 2017 Institute of Materials, Minerals and Mining. Published by Taylor & Francis on behalf of the Institute. The surface properties of Tyranno® Si–Al–C (SA) fibre (mean length: 0.7 mm) were modified from hydrophobic to hydrophilic nature by acid treatment of carbon-coated SA fibre, in order to enhance dispersibility or fracture toughness within silicon carbide (SiC) matrix. Two types of carbons, i.e. amorphous carbon and graphite carbon, were used to coat the surface of SA fibres (SA(AC) and SA(GC) fibres, respectively) by the pyrolysis of polyvinyl alcohol at 500°C for 30 min and 1800°C for 30 min, respectively. Then, carboxyl groups were formed on the SA(AC) and SA(GC) fibre surfaces through acid treatment (concentrated H 2 SO 4 and HNO 3 ) at room temperature. Owing to the acid treatment, SA fibre could be homogeneously mixed with SiC particles in polar solvent (acetone). The fracture toughness of SiC composites containing 40 mass% of acid-treated SA(GC) fibre (PVA/SA ratio = 2.5) hot-pressed at 1800°C for 60 min attained 8.3 MPa m 1/2 .